Atividades inovativas em indústrias de baixa e média-baixa tecnologias: um exame dos mecanismos de difusão da inovação - Fornari, Vinicius Cardoso de Barros [UNESP]; Gomes, Rogério [UNESP]; Morceiro, Paulo César [UNESP] (Nova Economia, 2014)
This study evaluates the characteristics of technological innovation from the assumption that this phenomenon is part of a process composed of different modes of production of technical and scientific knowledge. In order to do this, we will also examine a number of other activities made within the firm, some of them closely related to the diffusion of technology, besides the "traditional" research and development (R&D). Hence, the article focuses on the discussion of innovation in Low and Medium-low technology (BeMB) industries. For the examination of the characteristics of innovative activities, we confront the industries of some countries using data from the Pesquisa de Inovação Tecnológica (PINTEC, 2010) and the Community Innovation Survey (CIS,2009) for Brazilian companies and countries of the European Union, respectively. The findings indicate that there are significant differences in the characteristics of innovation in different countries and industries; and suggest important structural and institutional factors as determinants of technological activities.

Este estudo avalia as características da inovação tecnológica a partir do pressuposto de que esse fenômeno é parte de um processo composto por diferentes modos de produção de conhecimentos técnico-científicos e de aprendizados. Para isso, além da "tradicional" pesquisa e desenvolvimento (P&D), examinamos um conjunto de atividades desenvolvidas no âmbito da firma. Nessa perspectiva, o artigo prioriza a discussão sobre a inovação em indústrias de baixa e média-baixa tecnologias (BeMB). Para o exame das características das atividades inovativas, confrontamos as indústrias de países selecionados utilizando os dados da Pesquisa de Inovação Tecnológica (PINTEC, 2010) e da Community Innovation Survey (CIS, 2009) para empresas brasileiras e da União Europeia, respectivamente. As conclusões indicam diferenças expressivas nas características de inovação dos diferentes países e indústrias e sugerem condicionantes institucionais e estruturais como determinantes das atividades tecnológicas.
Keywords: atividades inovativas; difusão da inovação; indústrias de baixa e média-baixa tecnologias; innovative activity; technological diffusion; low and medium-low technology industries